Preeclampsia with Acute Pulmonary Edema - Gunawan, Yuliana Wydia; Purwoatmojo, Sunarko; Prasetyo, Anton Tri; Pamungkas, Bambang (Indonesian Socety of Obstetrics and Gynecology, 2025)
Objective: Describe the initial management for severe pre-eclampsia complicated with acute pulmonary edema. Methods: A case report. Case: 41 years old woman, G5P4A0, unknown gestational age, admitted with headache, dyspnea, and unconsciousness. The patient denied a history of past illness. Vital signs were checked, and crisis hypertension, tachypnea, tachycardia, and low oxygen saturation were obtained. Physical examination showed audible lung crackles and leg edema. Proteinuria +3 was detected. For initial management, the patient was given oxygen with Jackson-Rees bagging, Nicardipine drip, MgSO4 injection, and Furosemide injection. After the patient was fully conscious and stable in the ICU, the patient reported contractions with pelvic examination marked 8 cm dilatation. The patient underwent vaginal delivery and gave birth to a male, BW 2900gram, BL 47cm, APGAR 3/8. Discussion: Increased plasma volume, cardiac output, vascular permeability, peripheral vascular resistance, and decreased oncotic pressure are the causes of pulmonary edema in preeclampsia. According to Wallace et al, lowering blood pressure, giving adequate oxygen, and fluid restriction are the main management of pulmonary edema in preeclampsia. The correct initial management in the ER gives a good output on this case report. Conclusion: Initial management of acute pulmonary edema in pre-eclampsia patients should be done correctly, consequently decreasing maternal and fetal morbidity and mortality. Keywords: pregnancy, severe pre-eclampsia, pulmonary edema.